HUKUM PIDANA DAN KAITANNYA DENGAN PENGGUNAAN MEDIA SOSIAL - Natasya Serepina Parhusip (Fakultas Hukum Universitas Kristen Indonesia, 2015)
To date the growing use of technology is evidenced by the mushroomed of of a good number of social media such as Facebook, Twitter, Path, MySpace and so on. The public response towards the existence of the social media can be seen in the increasing number of social media users. Utilizing social media, everyone has freedom to express themselves through activities on the internet such as making comments and uploading various things. Despite its advantages, social media has sometimes become a stumbling block for users. One of the frequent issues arising in the usage of social media is offensive acts as a result of the activities in the social media. Therefore, the knowledge as to what extent users can express its aspiration in the social media is important which is strongly related to the law education to public. This paper elaborates cases of offensive acts occurred in the social media which are considered against the law particularly in Indonesian contexts. This paper further tries to analysis the relationship between the rule of criminal law and the cyberlaw in Indonesia. Kata kunci : Hukum Pidana dan Media sosial